Arbitration Agreement Provisions in Oil Franchise Contracts Disputes - Comparative Study – Upon Application to GCC Countries - Badwi, Fadwa Mohammed Ali (Journal of Economic, Administrative and Legal Sciences, 2024)
The arbitration agreement represents the basic route for the disputing parties concerning oil Franchise contracts to resort to arbitration rather than to the judiciary ways, as this agreement is the basic regulator of arbitration proceedings. The aim of the study is to set out the arbitration agreement’s provisions concerning oil Franchise contracts. The study therefore discussed the concept of the arbitration agreement, its shapes, with reference to its terms, its effects and the reasons which may lead to its termination in the oil Franchise contract in accordance with the legislation of the GCC States. The study used the comparative analytical inductive methodology to collect, analyze and compare data from the sources and texts of the legislation under consideration, for getting clear results. By listing the study’s topics, the study concluded some results, prominent among them: 1-There is a consensus between the legislations under consideration that the disputing parties concerning oil Franchise contracts may have recourse to an arbitration agreement concerning the disputes raised by this contract by resolution through arbitration rather than the ordinary judiciary. 2-There is no unified agreement between the GCC countries which regulate the arbitration agreement in oil Franchise contracts.